Reliability of 5-km Running Performance in a Competitive Environment. Issue 1 (2nd January 2017) - Hurst, Philip; Board, Lisa
ABSTRACT: The aim of this study was to examine the reliability of a 5-km time-trial during a competitive outdoor running event. Fifteen endurance runners (age = 29.5 ± 4.3 years, height = 1.75 ± 0.08 m, body mass = 71.0 ± 7.1 kg, 5-km lifetime personal best = 19:13 ± 1:13 minutes) completed two competitive 5-km time-trials over 2 weeks. No systematic differences in run time between Trial 1 and Trial 2 were reported (Trial 1: 1, 217 ± 85 sec, 95% CI [1, 170, 1, 264]; and Trial 2: 1, 216 ± 79 sec, [1, 172 to 1, 260], p  = .855). Absolute reliability, expressed as the typical error (TE; 14.7 sec, 95% CI = 11.3–21.4 sec) and coefficient of variation (CV; 0.95 ± 0.65%, [0.59–1.31]) confirms the reliability of 5-km running performance in a competitive time trial.